Pengaruh Green Intellectual Capital, Dan Leverage Terhadap Kinerja Keuangan Dengan Transparansi Sebagai Variabel Pemoderasi (Studi Kasus: Sektor Pertambangan Di Negara ASEAN (Indonesia, Malaysia, Dan Thailand) Periode 2015-2019) - Refany Novia Siboro (BADAN PENERBIT STIEPARI PRESS, 2023)
The research objectives include (1) This study aims to analyze the influence of the Green Intellectual Capital Mechanism on Financial Performance (2) This study aims to analyze the effect of Leverage on Financial Performance (3) This study aims to analyze the influence of Green Intellectual Capital on Financial Performance moderated by Transparency (4) This study aims to analyze the influence of Leverage on Financial Performance moderated by Transparency. The research was conducted on 31 manufacturing companies listed on the Stock Exchange (Indonesia, Malaysia and Thailand) for the 2015-2019 period. Selection of the sample used using purposive sampling method. The aim of this research is to determine the Effect of Green Intellectual Capital and Leverage on Financial Performance with Transparency as a Moderating Variable. The results of Indonesia's Green Intellectual Capital research have no effect on Financial Performance while Malaysia and Thailand Green Intellectual Capital have a positive effect on Financial Performance. The results of the Leverage Variable research in Indonesia yield different results. The Indonesian test results yielded Leverage that had no effect on Financial Performance, while Malaysia and Thailand produced Leverage that had a significant effect on Financial Performance. Transparency moderates Green Intellectual Capital and Leverage in Malaysia and Thailand, while Indonesia produces Transparency that does not moderate the relationship between Green Intellectual Capital and Leverage on Financial Performance. Transparency moderates Leverage in Malaysia and Thailand while Indonesia and produces Transparency does not moderate the Leverage relationship to Financial Performance.